2008
DOI: 10.1002/jbm.a.32116
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cell adhesion and proliferation in response to ceramic chemistry and nanoscale topography

Abstract: Modification of the chemistry and surface topography of nanophase ceramics was used to provide biomaterial formulations designed to direct the adhesion and proliferation of human mesenchymal stem cells (HMSCs). HMSC adhesion was dependent upon both the substrate chemistry and grain size, but not on surface roughness or crystal phase. Specifically, cell adhesion on alumina and hydroxyapatite was significantly reduced on the 50 and 24 nm surfaces, as compared with the 1500 and 200 nm surfaces, but adhesion on ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 36 publications
3
91
0
1
Order By: Relevance
“…26 The cell adhesion results of this study indicate that MG-63 osteoblast-like cells adhered better to the n-CDHA-MAC composite with 30 wt% n-CDHA than to the MAC and to the tissue culture plate control within the first 4 hours. The superior ability of MG-63 cells to attach to the composite probably reflects the differing material surface features of the composite and the MAC.…”
Section: Cytocompatibility Cell Adhesionmentioning
confidence: 64%
See 1 more Smart Citation
“…26 The cell adhesion results of this study indicate that MG-63 osteoblast-like cells adhered better to the n-CDHA-MAC composite with 30 wt% n-CDHA than to the MAC and to the tissue culture plate control within the first 4 hours. The superior ability of MG-63 cells to attach to the composite probably reflects the differing material surface features of the composite and the MAC.…”
Section: Cytocompatibility Cell Adhesionmentioning
confidence: 64%
“…The nanosized calcium-deficient hydroxyapatite in the MAC expose the composite surfaces that had additional surface properties, which improved cell adhesion. 26,27 Cell viability…”
Section: Cytocompatibility Cell Adhesionmentioning
confidence: 99%
“…The thickness of the wet films was about 450 μm. The base film (i.e., p(HEMA-GMA)-OH) density was measured to be 1.19 g/cm 3 . The FTIR studies were presented as supplementary data (Supplementary Table 2).…”
Section: Synthesis Modification and Characterization Of The Modifiedmentioning
confidence: 99%
“…The properties of hydrogels such as the functional groups, chemical composition, hydrophilic-hydrophobic balance, surface morphology, and presence of adherent proteins are essential for the regulation of cellular interactions. Therefore, the performance of a hydrogel material relies highly upon the properties of the boundaries in tissue engineering applications because the interactions between the hydrogel materials and environments occur mainly on its surfaces [1][2][3][4]. The hydroxyethyl methacrylate (pHEMA) hydrogel possesses good biocompatibility as evidenced by its large scale use in biomedical and biotechnological applications such as contact lenses, drug delivery systems, and soft tissue prosthesis [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of mechanical stimulus on cell behavior is affected by intrinsic properties of the cell and properties of the ECM as well as extrinsic forces acting on the cell (Chou et al 2009;Dulgar-Tulloch et al 2009;Jaalouk and Lammerding 2009;McCullen et al 2010b). Even when considering strategies for the rather specific purpose of bone engineering with cells derived from human fat, there are several parameters for influencing the osteogenic differentiation; for instance, media formulation (Lindroos et al 2010;Lund et al 2009), oxygen tension (He et al 2010), harvest location, and sex of donor (Aksu et al 2008) have all been reported to have an effect on the osteogenic potential of ASCs.…”
Section: Consideration Of Apparent Conflicts In Findingsmentioning
confidence: 99%